Bone mineral density and sex hormone binding globulin as potential mediators of the causal effect of urolithiasis on osteoporosis risk: a Mendelian randomization - Guo, Jiawei; Chen, Xinyu; Yi, Xinping; Dou, Yongqi; Xiong, Yongjiang; Zhao, Tao (Frontiers in Endocrinology, 2025)
ObjectiveOsteoporosis (OP) and urolithiasis (UL) are two metabolic diseases that are prevalent globally. Previous observational studies have found a relationship between these two diseases that increases the risk of each other, but whether there is a direct causal link is still unclear. Currently, research on the mechanisms of these two diseases mainly focuses on external factors such as diet and environment. Thus, this study used two-sample mendelian randomization (TS-MR) in conjunction with mediation analysis to explore the causal relationship between OP and UL and their potential mechanisms. Mediators included total body bone mineral density (T-BMD), sex hormone binding globulin (SHBG), serum 25-hydroxyvitamin D (serum 25(OH)D) levels, and calcium supplements.MethodWe acquired UL-related and BMD-related single nucleotide polymorphisms (SNPs) from the MRC IEU Open Genome-Wide Association Study (GWAS) database. The primary SNPs data of osteoporosis were from the FinnGen database. To clarify the mediators involved in the link between OP and UL, we performed a MR investigation. The primary approach to analysis was inverse variance weighting (IVW). In addition, we also used another osteoporosis data from UK biobank (UKB) to further verify the mediating role.ResultsWe discovered that there was a 14% increase in the incidence of OP in UL patients using the IVW approach. (FinnGen: OR = 1.1491,95% CI: 1.0544-1.2523; UKB: OR = 1.1339,95% CI: 1.0266-1.2523). Among different age groups, except for the 15-45 age group, we observed that UL increased the risk of low bone mineral density. Similarly, consistent results were also observed in bone mineral density at different sites. Mediation analysis showed that 50% of the effect of UL on OP was mediated by BMD levels (FinnGen:49.68%; UKB:56.45%). In addition, we also observed an important mediating effect between sex hormone binding globulin (SHBG) on UL and an increased risk of OP, but with a lower proportion of mediators (FinnGen:2.406%; UKB:2.595%). Furthermore, we also found decreased serum 25 (OH) D levels in UL patients, but not its mediating effect.ConclusionsIn conclusion, the study establishes a direct causal link between urolithiasis and OP, independent of environmental factors. Furthermore, mediation analysis showed that bone density and SHBG levels partially mediated the risk of OP in UL patients, suggesting that both mediators may be involved in the mechanism of UL-induced OP. These findings broaden the understanding of the link between the UL and the OP. Thus, regardless of lifestyle, urolithiasis patients should remain vigilant about the risk of OP and consider regular OP screening.